Pakistan Marble Industry Challenges: Opportunities for China in Pakistan - Mansoor, Yasir; Syed, Nadeem A. (JISR management and social sciences & economics, 2012)
The phrase world has now become a global village is rightly indicative of the fruitful effects and outcomes for entrepreneurs as far as their growth and profit margin are concerned. This study will analyze the marble industry of Pakistan with respect to China. What are the export potentials of Pakistani industry in China? Do we supply marble according to their need? Is our marble best in quality? Will our export increase in future to China? Is this industry has potentials in contributing to our economy and GDP to a larger extent? This variety of inquiry will be undertaken in this study. However, we believe that there are huge gaps between demand and supply of marble to China and these gaps badly affect our export and economy as well. It is true that our exports of marble to China are not according to our reserves i.e. 160 million tons and our export of marble to China is only $ 55 million. This is 3.6% of their total imports of marble. While conducting a forecasting analysis, it has been proven that the export of marble is increasing in past and also shows a growing trend in upcoming future. Some structured interviews have also been taken which demonstrate that our primary and secondary data are equivalent. We export most of our marble to China but still we cannot supply according to the demand because of various factors. In marble industry export, China is the major buyer and it gives a great boost to our economy. The export orders are receive mostly from China and 63% people strongly agree that exports of marble from Pakistan to China are not as much as it should have been but if we can sort out problems like tribal fights, lack of technological infrastructure, semi trained workers and simultaneously government policies need to be streamlined as they can facilitates entrepreneurs and hence export can be increased to a larger extent.